Shake‐table test performance of an inertial force‐limiting floor anchorage system. (25th May 2018) - Zhang, Zhi; Fleischman, Robert B.; Restrepo, Jose I.; Guerrini, Gabriele; Nema, Arpit; Zhang, Dichuan; Shakya, Ulina; Tsampras, Georgios; Sause, Richard
Summary: A new floor connecting system developed for low‐damage seismic‐resistant building structures is described herein. The system, termed Inertial Force‐Limiting Floor Anchorage System (IFAS), is intended to limit the lateral forces in buildings during an earthquake. This objective is accomplished by providing limited‐strength deformable connections between the floor system and the primary elements of the lateral force‐resisting system. The connections transform the seismic demands from inertial forces into relative displacements between the floors and lateral force‐resisting system. This paper presents the IFAS performance in a shake‐table testing program that provides a direct comparison with an equivalent conventional rigidly anchored‐floor structure. The test structure is a half‐scale, 4‐story reinforced concrete flat‐plate shear wall structure. Precast hybrid rocking walls and special precast columns were used for test repeatability in a 22‐input strong ground‐motion sequence. The structure was purposely designed with an eccentric wall layout to examine the performance of the system in coupled translational‐torsional response. The test results indicated a seismic demand reduction in the lateral force‐resisting system of the IFAS structure relative to the conventional structure, including reduced shear wall base rotation, shear wall and column inter‐story drift, and, in some cases, floor accelerations. These results indicate the potential for the IFAS to minimize damage to the primary structural and non‐structural components during earthquakes.